Penerapan model pembelajaran kooperatif tipe think talk write (ttw) untuk meningkatkan pemahaman konsep keliling dan luas bidang datar pada peserta didik kelas iii sekolah dasar - Tiyas Herawati Mu'arifah; Hasan Mahfud; Joko Daryanto (Didaktika Dwija Indria, 2019)
Abstract. The goals of the research was to improve understanding of the concept of circumference and the extent of flat fields through  use of the Think Talk Write model in third grade students of SD N Pajang III No. 206 Surakarta 2018/2019 school year. Classroom Action Research is conducted in two cycles, every cycle consisting of two meeting with four stages, among others  planning, action, observation, and reflection. The subject of this study were teachers and third grade students, amounting to 36 students. This study uses observational techniques, tests, documentation anf interview. Data analysis technique through data Miles and Huberman analysis models with steps of data collection, data reduction, data display and conclusion. Data validity test techniques use content validity, source triangulation and technical triangulation. The result showed that the average score pre-action class 47 score with classical completenes was 2.77%, increasing to 56.86 with percentage of completeness is 27.77% in the first cycle and increasing again to 80.16 with classical completeness of 83.33% in cycle II. Source from research result, it can be concluded that through the application of the Think Talk Write model can improve understanding of the concept of circumference and the extent of flat fields in class III SD N Pajang III No. 206 Surakarta 2018/2019 school year.Keyword: understanding of the concept of circumference and the extent of flat fields, Think Talk Write models, elementary school